Development of Durian Leather and Determination of its Flavour Retention During Processing and Storage - Irwandi, (1996)
Durian (DuriO zibethinus Murr) is a popular seasonal fruit grown in many parts of South-East Asia. Malaysia, Thailand and Indonesia are major producers of this fruit in the world. Today, durians are not only planted in home garden but also grown commercially in large-scale plantation to meet the local and export demands. Normally, durians are eaten shortly after harvest in fresh form as it quickly turns sour and rancid due to some chemical changes that follow. To a lesser extend, durian is also processed into products like lempuk (durian cake) and tempoyak (fermented durian), two traditional products widely consumed in Malaysia and Indonesia. However, these product are not commercially produced in large quantities. Meanwhile, fruit leather, a product prepared by dehydration of fruit puree, is an established product particularly in the North American and European markets; however it is relatively unknown product in Malaysia. Therefore, the development of a new fruit leather from durian could be an alternative to increase the commercial value of durian. Four aspects in the development of durian leather were conducted in this study. These were preliminary study on the development of durian leather, optimization of formulation and drying conditions of durian leather, product stability during storage and determination of the retention of its flavouring components during processing and storage. fu the preliminary study, the results showed that processing of durian leather was feasible to diversifY the use of durian. Proximate composition of the leather was comparable to other fruit leathers in the market. The product was relatively stable and showed low mould counts and organoleptically acceptable in all attnlmtes studied during three months storage.Optimizations of ingredient formulation and drying conditions were carried out using Response Surface Methodology (RSM) technique. The results based on sensory evaluation showed that the most acceptable formulation was an ingredient combination of 10% glucose syrup solid, 5% sucrose, 2.67% hydrogenated palm oil and 0.45% soy-lecithin added into durian aril for the preparation of durian leather. Optimum drying conditions were 50°C for 12.6 h for oven-dried leather, and 52.5°C for 10 h for cabinet-dried leather. A storage study on the optimum formulation and processing conditions indicated that durian leather was a stable product up to 12 weeks storage. All samples packed in four different types of packaging materials i. e. laminated aluminium foil (LAF), high-density polyethylene (HDPE), low-density polyethylene (LDPE) and polypropylene (PP), were shown to be organoleptically acceptable by the panelists. LAF, however, was proven to be the finest packaging material in maintaining the stability of durian leather during storage.